Wetenschappelijk onderzoek op het gebied van het Nieuwe Testament en grensgebieden in Nederland en Nederlandstalig Belgie, 1993- 1999 1 - Jonge, Marinus de (Hervormde teologiese studies, 1999)
Scientific research on the New Testament and related fields in the Netherlands and Dutch-speaking Belgium, 1993-1999. The article gives an overview of recent and current New Testament research in the Netherlands and Belgium. The institutions and circumstances within which research is done, are discussed. The article points out that theological faculties function within an increasingly secularising society. In spite of this, and the problems the churches are experiencing, there still is a remarkable interest in religion and theology both within and outside of church and university circles. Research trends include a focus on the cultural environment of early Christianity, the history and literature of Christianity ater the first century and a linguistic and literary approach. The interest in Biblical theological issues is much more limited. These trends and the researchers working in the various fields are discussed in detail. The article concludes that much has been done in the field of New Testament research in the Dutch-speaking world in spite of fairly unfavourable circumstances.